PENGARUH MUTASI DAN MOTIVASI KERJA TERHADAP KINERJA PEGAWAI - Dian Ratih Fikamissa Falegy; Aburrahman Kader; Sudirah Sudirah (Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
This study was aimed to determine: (1) employees transfer in BPK Representatives of North Maluku Province; (2) work motivation at BPK Representative of North Maluku Province; (3) performance in BPK Representatives of North Maluku Province; (4) the effect of employees transfer on the performance of BPK staff of the Representatives of North Maluku Province; (5) work motivation towards the performance of BPK Representatives of North Maluku Province (6) employees transfer and work motivation towards the performance of BPK Representatives of North Maluku Province. The problem underlying this study is that the main performance indicator has not yet been reached in the North Maluku Provincial Representative BPK, inconsistent employees transfer policies, and decreased of employees discipline. The study was conducted on civil servants in the BPK Representative of North Maluku Province. This research uses quantitative approach with descriptive associative research. Data collection procedures are carried out through a questionnaire as the main data source, and are equipped with interviews / observations and document analysis. The study sample counted 49 people and the population was 67 people. The data analysis technique used in this study is path analysis. The results of this study indicate that: (1) perception of employees transfers in BPK Representatives of the Province of North Maluku is low; (2) the work motivation of employees at BPK Representatives of North Maluku Province is very high; (3) the performance in the North Maluku Province BPK Representative was high; (4) employees transfer is not significant to employees performance with the value of -tvalue>-ttable (-1.664> -2.013) significance of 0.107; (5) work motivation is significant on employees performance with tvalue>ttable (16,554> 2,013) significance of 0,000; (6) employees transfer and work motivation have significant effect on employees performance with a calculated Fvalue> Ftable (140,178> 3,200) significance of 0,000. The R square is 0.859 which means employees transfer variables and motivation variables together have a contribution of 86.9% on performance. The conclusion from this study is that employees transfers doesn’t have significant effect on employees performance partially. Work motivation have positive and significant effect on employees performance. Employees transfer and work motivation together have a significant contribution on employees performance.